Student perspectives on interdisciplinary learning in public health education: insights from a mixed-methods study - Lim, Raymond Boon Tar; Tan, Claire Gek Ling; Voo, Kelly; Lee, Yock Leng; Teng, Cecilia Woon Chien (Frontiers in Public Health, 2024)
Interdisciplinary learning is essential for equipping future health professionals to tackle the complexities of contemporary public health. This mixed-methods study investigates the experiences and perspectives of undergraduate public health students in Singapore on interdisciplinary learning in higher education and employed a convergent parallel design by combining a cross-sectional survey with in-depth interviews. Quantitative data were used to assess the relationship between students’ exposure to interdisciplinary learning and its perceived value, while qualitative analysis explored key themes related to facilitators and barriers. Among 52 survey respondents and 11 interview participants, nearly half regularly engaged in interdisciplinary learning. Students with greater exposure to interdisciplinary experiences demonstrated more positive perceptions. Facilitators identified included career development opportunities, faculty engagement, and diverse learning experiences. Barriers such as disciplinary disconnects and the challenge of managing varied skill sets were also highlighted. This study provides valuable insights into interdisciplinary learning in higher education pertaining to public health, particularly within the context of health professions training. The findings suggest that enhancing curricular design, integrating interdisciplinary approaches more effectively, and increasing faculty support can address identified barriers and better prepare students for the demands of their future public health careers.